Work agency in the machine word - Costa, Massimiliano (Formazione & insegnamento, 2019)
Action working in the new productive contexts takes on a highly subjective, therefore reflective and creative value, able to guide the person in defining and implementing his own life project, promoting personal self-realization. The essay analyzes the change in work behavior by linking it to the educational and transformational value of learning as it emerges from the OECD Framework 2020.